From Cyclopentasilane to Thin-Film Transistors - Gerwig, Maik; Ali, Abid Shaukat; Neubert, David; Polster, Sebastian; Bohme, Uwe; Franze, Georg; Rosenkranz, Marco; Popov, Alexey; Ponomarev, Ilia; Jank, Michael; Viehweger, Christine; Brendler, Erica; et al. (Advanced Electronic Materials, 2021)
Cyclopentasilane (CPS) has been studied as an liquid precursor for the deposition of thin silicon films for printed electronics and related applications. The processing involves a UV-induced prepolymerization of CPS followed by liquid deposition and low-temperature thermolysis. An insight into the oligomer and polymer formation including crosslinking in solution using Si-29 NMR spectroscopy and electron spin resonance spectroscopy is reported. Formation of SiH (T-units) and SiH3 (M-units) is observed as well as short-lived paramagnetic species. Additionally, the polymerization is followed by Raman spectroscopy. Reactive molecular dynamics simulations are applied to develop a theoretical model for the CPS-ring-opening and crosslinking steps. The experimental and computational data correspond well to each other and allow insight into the mechanism of polymer formation. The processing steps include spin-coating, thermal drying, and conversion to amorphous silicon, H-passivation, and fabrication of a CPS-derived thin-film transistor (TFT), without intermediate silicon crystallization. Further improvement is gained by using tetralene as a solvent, leading to a reduction of the time-consuming polymerization step by one order of magnitude compared to cyclooctane. The overall quality and characteristics of the CPS-derived spin-coated silicon thin films correspond to standard plasma enhanced chemical vapor deposition-derived devices with respect to performance levels.
CRIS-Team WoS Importer:2021-01-08